2018
DOI: 10.18632/oncotarget.23830
|View full text |Cite
|
Sign up to set email alerts
|

Combining expression of GPC3 in tumors and CD16 on NK cells from peripheral blood to identify patients responding to codrituzumab

Abstract: BackgroundCodrituzumab, a monoclonal antibody targeting an oncofetal protein glypican-3 (GPC3) expressed on cell surface of hepatocellular carcinoma (HCC) induces antibody-dependent cellular cytotoxicity (ADCC) and inhibits tumor growth in preclinical studies. Based on this mechanism, tumor GPC3 expression and CD16 expression on NK cells, which are the effector cells of ADCC, were investigated to correlate with codrituzumab's clinical efficacy in patients with advanced HCC.ResultsJoint analyses of the two biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Additional antibodies potentially involving NK cell activation and ADCC as mechanism of action were reviewed by Wang et al (175). More recent reports of NK cell activating antibodies with varying combinatorial treatments are listed in Table 2, including anti-SLAMF7, Elotuzumab, for multiple myeloma (258); anticathepsin-D, F1, for Triple Negative Breast Cancer (179); anti-GD2, Dinutuximab and hu14.18K322A, for neuroblastoma (259,260); anti-PD-L1, Avelumab, for Triple Negative Breast Cancer (261); anti-CD38, Daratumumab, for multiple myeloma (262, 263); anti-GPC3, Codrituzumab, for hepatocellular carcinoma (264); and anti-CD33, BI 836858, for AML (265).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…Additional antibodies potentially involving NK cell activation and ADCC as mechanism of action were reviewed by Wang et al (175). More recent reports of NK cell activating antibodies with varying combinatorial treatments are listed in Table 2, including anti-SLAMF7, Elotuzumab, for multiple myeloma (258); anticathepsin-D, F1, for Triple Negative Breast Cancer (179); anti-GD2, Dinutuximab and hu14.18K322A, for neuroblastoma (259,260); anti-PD-L1, Avelumab, for Triple Negative Breast Cancer (261); anti-CD38, Daratumumab, for multiple myeloma (262, 263); anti-GPC3, Codrituzumab, for hepatocellular carcinoma (264); and anti-CD33, BI 836858, for AML (265).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…In the phase II trial of codrituzumab vs. placebo, median PFS was 2.6 months vs. 1.5 months, respectively, with a hazard ratio [HR] 0.97 and p = 0.87, and median OS was 8.7 months vs. 10 months, respectively, with HR 0.96 and p = 0.82 [65]. Nevertheless, sub-analysis of the results of the phase II trial and another study indicated that codrituzumab showed prognostic merit for HCC patients with a high immunogenicity related to ADCC and a high expression of GPC3 [65,66].…”
Section: Clinical Trials Of Gpc3 Targeting Therapymentioning
confidence: 99%
“…The amplified NK cell surface activating receptor CD107A was significantly up-regulated and could secrete more IFN-γ, and had highly cytotoxicity to many kinds of cancer cells in vitro and in vivo. Subsequently, Chen et al [93] explored the effects of CD16 overexpression in NK cells induced by monoclonal antibodies against the tumor embryo protein GPC3 (glypican-3) target to HCC. The results of immunohistochemistry (IHC) showed that GPC3 and CD16 could be expressed on tumor cells and NK cells of peripheral blood, respectively.…”
Section: Nkg2d Signaling Induces High Expression Of Cd16 On Nk Cells mentioning
confidence: 99%